The essence and significance of remuneration as a fundamental category of social and labour relations. - Kulikov, P.; Dropa, I. (Ways to Improve Construction Efficiency, 2023)
This article is devoted to the analysis of contemporary concepts, the clarification of the essence of the category "compensation," its significance in the process of regulating social and labor relations, and the subsequent improvement of the mechanisms for its regulation under modern conditions. The analysis of the current Ukrainian legislation demonstrates that there is no clearly defined concept of ‘remuneration of labour’ in such key legal acts as the Law of Ukraine ‘On Remuneration of Labour’ and the Labour Code of Ukraine. The existing definitional vacuum regarding the concept of ‘remuneration of labour’ in the current legal framework gives rise to a multiplicity of interpretations. The article examines the historical background of the term ‘remuneration of labour’ and its interpretation by scholars. The analysis of the views of Ukrainian researchers can generally be classified and systematised into the following main areas: economic, social, motivational, cost, accounting, organisational and managerial, legal and psychological. The article characterizes the roles and key functions of compensation in social and labor relations: reproductive, regulatory, social, motivational, and optimizing. The fundamental nature of compensation is due to its role as the price of labor, employee income, enterprise costs, a tool for investing in human capital, and a regulator of socioeconomic processes. The authors note that employers, seeking to reduce costs, often neglect social aspects, which can lead to social tension and decreased productivity. The authors conclude and agree with researchers who consider the concept of ‘remuneration’ to be broader than “wages”, as it combines all aspects of interaction between the employee and the employer aimed at creating conditions for economic motivation, social stability and reproduction of labour force within the labour process. Remuneration is a comprehensive system of social and economic relations between employers and employees, which includes mechanisms, methods and processes for providing monetary and material remuneration for the use of labour. Unlike “wages”, remuneration also covers the system of regulation of labour relations, determination of labour incentive mechanisms, organisational and legal aspects that regulate the relationship between production results, labour productivity and the level of remuneration.